Diagnostic preparedness for infectious disease outbreaks. Issue 10108 (11th November 2017) - Perkins, Mark D; Dye, Christopher; Balasegaram, Manica; Bréchot, Christian; Mombouli, Jean-Vivien; Røttingen, John-Arne; Tanner, Marcel; Boehme, Catharina C
Summary: Diagnostics are crucial in mitigating the effect of disease outbreaks. Because diagnostic development and validation are time consuming, they should be carried out in anticipation of epidemics rather than in response to them. The diagnostic response to the 2014–15 Ebola epidemic, although ultimately effective, was slow and expensive. If a focused mechanism had existed with the technical and financial resources to drive its development ahead of the outbreak, point-of-care Ebola tests supporting a less costly and more mobile response could have been available early on in the diagnosis process. A new partnering model could drive rapid development of tests and surveillance strategies for novel pathogens that emerge in future outbreaks. We look at lessons learned from the Ebola outbreak and propose specific solutions to improve the speed of new assay development and ensure their effective deployment.